Resource Recovery from Abandoned Mine Drainage Galleries via Ion Exchange: A Case Study from Freiberg Mining Area, Germany - Janith Abeywickrama; Katayoun Karimi; Marlies Grimmer; Nils Hoth; Carsten Drebenstedt (Recycling)
The discharge of metal-loaded mining-influenced waters can significantly pollute downstream water bodies for many kilometers. Addressing this issue at the earliest discharge point is crucial to prevent further contamination of the natural environment. Additionally, recovering metals from these discharges and other sources of contamination can reduce the environmental impacts of mining and support the circular economy by providing secondary raw materials. This study focused on optimizing zinc recovery from mining-influenced water in the Freiberg mining region in Germany, where significant loads of zinc are released into the Elbe River. By employing pretreatment techniques, conducting 100 mL scale ion-exchange column experiments, and refining the regeneration process, we aimed to identify optimal conditions for efficient zinc removal and recovery. Initial tests showed that aminophosphonic functionalized TP 260 resin had a high affinity for aluminum, occupying 93% of the resin’s capacity, while zinc capacity was limited to 0.2 eq/L. To improve zinc recovery, selective precipitation of aluminum at pH 6.0 was introduced as a pretreatment step. This significantly increased the zinc loading capacity of the resin to 1 eq/L. Under optimal conditions, a concentrated zinc solution of 18.5 g/L was obtained with 100% recovery. Sulfuric acid proved more effective than hydrochloric acid in eluting zinc from the resin. Further analysis using SEM-EDX revealed residual acid on the resin, indicating a need for additional study on long-term resin performance and capacity variation. The research also highlighted the environmental impact of the Freiberg mining area, where three drainage galleries currently contribute nearly 85 tons of zinc annually to the Elbe River. This study underscores the feasibility of efficient zinc recovery from these point sources of pollution using advanced ion-exchange processes, contributing to circular economy efforts and environmental conservation.